The canyon of Haidamatskyi Iar in the village of Busha: Geotourism assessment - Yulian Braychevskyy; Volodymyr Korinnyi; Olga Kovtoniuk; Nataliia Pohorilchuk (International Journal of Geoheritage and Parks)
The purpose of this work was to quantitatively assess the Haidamatskyi Iar canyon as a geotourism site, draw attention to geotourism development outside of the Carpathian Mountains region in Ukraine, and further contribute to the assessment methods choice and application debate. We based our analysis on field observations and combined three evaluation algorithms, namely the Kubalikova's method, the geosite assessment model, and the Brilha method. For each algorithm, we presented results as a percentage of the maximum for easier comparison. Our assessment concluded that the Haidamatskyi Iar canyon received rather high scores with all three approaches (86.11% with the Kubalikova's method, 76.88% with Brilha's method, and 62.96% with the geosite assessment model), revealing its strong potential as a geological and geomorphological research and education site. Poor tourist infrastructure (due to the area's peripheral location) and lack of specialized promotional products highlighting geoeducational attractions of the area explained lower scores by the geosite assessment model. Overall, we concluded that the Haidamatskyi Iar canyon was a unique geomorphosite of regional and even national significance. It displayed a wide range of geological features, especially those related to weathering, fluvial, and Aeolian erosion. Its location next to a historical and cultural destination (the village of Busha) made it valuable for geotourism promotion. In the wider context of similar geoattractions in Central and Eastern Europe, our analysis demonstrated the benefits of choosing methods, which were previously applied to comparable geosites. Variation in assessment scores confirmed better reliability of simultaneous application of several assessment methods.